Continued wearing of gloves: a risk behaviour in patient care - M. Lindberg; B. Skytt; M. Lindberg (Elsevier, 2020)
Summary: Background: The wearing of gloves is included in the standard principles for preventing healthcare associated infections. A continued wearing of gloves may, however, result in the transmission of organisms instead of preventing infections. Few studies have explored how common it is for surfaces to be touched by potentially contaminated gloves. Methods: Secondary analysis of field notes from 48 hours of unstructured observations of healthcare personnel's actions during patient care. The new focus was on to what extent healthcare personnel wore gloves that should have been removed or changed, what surfaces were touched by contaminated gloves and what patient-related activities were involved. Results: A continued wearing of gloves occurred in about half of the observed episodes of patient care. On average, 3.3 surfaces were touched by contaminated gloves. The surfaces most frequently touched were 'unused single-use items', 'equipment controls/switches/regulators/flush buttons' and 'bed linen'. This occurred mostly while helping patients with 'personal hygiene', when performing 'test taking' or during procedures involving the operation of medical or other 'equipment'. Conclusion: The continued wearing of gloves during patient-related activities carries the risk of organism transmission, as the gloves touch many surfaces. The most critical moments seem to be when the use of gloves is considered essential. A better understanding of the motivators of improper glove-use behaviour is needed to develop interventions that rectify the improper use of gloves.